Activity of a novel sulfonamide compound 2-nitro-N-(pyridin-2-ylmethyl)benzenesulfonamide against Leishmania donovani - Dikhit MR; Purkait B; Singh R; Sahoo BR; Kumar A; Kar RK; Ansari MY; Saini S; Abhishek K; Sahoo GC; Das S; Das P (Dove Medical Press, 2016)
Manas R Dikhit,1,* Bidyut Purkait,1,* Ruby Singh,1 Bikash Ranjan Sahoo,2 Ashish Kumar,1 Rajiv K Kar,3 Md Yousuf Ansari,1,4 Savita Saini,1,5 Kumar Abhishek,1 Ganesh C Sahoo,1 Sushmita Das,6 Pradeep Das11Department of Molecular Parasitology and Biomedical Informatics, Rajendra Memorial Research Institute of Medical Sciences, Indian Council of Medical Research, Agamkuan, Patna, Bihar, India; 2Laboratory of Molecular Biophysics, Institute for Protein Research, Osaka University, Japan; 3Biomolecular Nuclear Magnetic Resonance and Drug Design Laboratory, Department of Biophysics, Bose Institute, Kolkata, West Bengal, 4Department of Pharmacoinformatics, 5Department of Biotechnology, National Institute of Pharmaceutical Education and Research, Hajipur, 6Department of Microbiology, All India Institute of Medical Sciences, Patna, Bihar, India*These authors contributed equally to this workAbstract: New treatments for visceral leishmaniasis, caused by Leishmania donovani, are needed to overcome sustained toxicity, cost, and drug resistance. The aim of this study was to evaluate the therapeutic effects of 2-nitro-N-(pyridin-2-ylmethyl)benzenesulfonamide (2NB) against promastigote and amastigote forms of L. donovani and examine its effect in combination with amphotericin B (AmB) against AmB-resistant clinical isolates. Effects were assessed against extracellular promastigotes in vitro and intracellular amastigotes in L. donovani-infected macrophages. Levels of inducible nitric oxide and Th1 and Th2 cytokines were measured in infected 2NB-treated macrophages, and levels of reactive oxygen species and NO were measured in 2NB-treated macrophages. 2NB was active against promastigotes and intracellular amastigotes with 50% inhibitory concentration values of 38.5±1.5 µg/mL and 86.4±2.4 µg/mL, respectively. 2NB was not toxic to macrophages. Parasite titer was reduced by >85% in infected versus uninfected macrophages at a 2NB concentration of 120 µg/mL. The parasiticidal activity was associated with increased levels of Th1 cytokines, NO, and reactive oxygen species. Finally, 2NB increased the efficacy of AmB against AmB-resistant L. donovani. These results demonstrate 2NB to be an antileishmanial agent, opening up a new avenue for the development of alternative chemotherapies against visceral leishmaniasis.Keywords: visceral leishmaniasis, AmB resistance, benzenesulfonamide, ROS, NO, Th1/Th2 cytokines